Host defense peptides clavanins A and MO reduce in vitro osteoclastogenesis - Ingrid Aquino Amorim; Stella Maris de Freitas Lima; Ana Paula de Castro Cantuária; Mirna de Souza Freire; Jeeser Alves de Almeida; Octávio Luiz Franco; Taia Maria Berto Rezende (Universidade Estadual de Campinas, 2021)
Aim: Several systemic diseases, such as periodontitis and apical periodontitis, can cause extensive bone resorption. Host defense peptides may have the potential for the development of novel therapies for the bone resorption process. This study evaluated the potential of host defense peptides clavanins A, MO, and LL-37 in in vitro osteoclastogenesis. Methods: RAW 264.7 cultures were stimulated with recombinant of receptor activator of nuclear factor kappa B ligand in the presence of different tested concentrations of host defense peptides, besides calcium hydroxide and doxycycline. Cellular viability, nitric oxide production, and a number of differentiated osteoclast-like cells were also evaluated. Results: Results showed that none of the substances were cytotoxic, except for 128 μg.mL-1 of doxycycline after 3 days. Host defense peptides, calcium hydroxide, and doxycycline did not interfere in nitric oxide production or downregulated it. An exception was observed in the presence of 2 μg.mL-1 of doxycycline, in which nitric oxide production was up-regulated. All host defense peptides were capable of reducing osteoclast-like cell differentiation. Conclusion: Host defense peptides clavanins A and MO demonstrated to be potential suppressors of osteoclastogenesis in vitro without interfering in cellular viability and nitric oxide production. These promising results need to be further analyzed in in vivo models of bone resorption.